Crustal subsidence observed by GRACE after the 2013 Okhotsk deep‐focus earthquake. Issue 9 (5th May 2015) - Tanaka, Yusaku; Heki, Kosuke; Matsuo, Koji; Shestakov, Nikolay V.
Abstract Coseismic gravity changes stem from (1) vertical deformation of layer boundaries with density contrast (i.e., surface and Moho) and (2) density changes of rocks at depth. They have been observed in earthquakes with Mw exceeding 8.5 by Gravity Recovery and Climate Experiment (GRACE) satellites, but those of M8 class earthquakes have never been detected clearly. Here we report coseismic gravity change of the 24 May 2013 Okhotsk deep earthquake (Mw8.3), smaller than the detection threshold. In shallow thrust faulting, factor (2) is dominant, while factor (1) remains secondary due to poor spatial resolution of GRACE. In the 2013 Okhotsk earthquake, however, factor (2) is insignificant because they occur at depth exceeding 600 km. On the other hand, factor (1) becomes dominant because the centers of uplift and subsidence are well separated and GRACE can resolve them. This enables GRACE to map vertical ground movements of deep earthquakes over both land and ocean.